Los contratos de construcción. La figura del contratista y su relación con el riesgo - Vásquez Rebaza, Walter (2017)
Despite its high complexity and significant presence in contemporary legal-economic transactions, construction contracts are, from a legal perspective, still part of a field rarely explored by national academics. In the present article, which is part of a long-term research on the subject, we will only analyze the typical components that characterize the activity of construction contractors. The aforementioned development is justified to the extent that it will help to understand and apply in an appropriate way the general (civil) and sectorial rules on the matter. In more detail, we hope that the conclusions of the present research shed light on the elucidation of the level of risk that contractors must assume in the development of their contractual services, given the peculiarities of their activity.